Merleau-Ponty y el sentido de lo político - Eiff, Leonardo (ARFIL y UNL, 2018)
This paper analyzes the sense of political in the thought of Merleau-Ponty. Three very known writings (Lecture de Montaigne, Note sur Machiavel and the prologue to Humanisme et terreur) are chosen to caracterize that point beyond the customary periodizations of his work. That nucleus condenses a notion of political as contingency and conflict where the Machiavelian root enters in a critical dialogue with the Marxist tradition. On the other hand, our conclusion explores the hypothesis that Merleau Ponty’s reflections about the concept of political are nourished by a notion of humanism that evades Heidegger's interpretation and it is connected with the republican saga of political humanism.